Single-parent immigrant families in Iceland : lives and educational experiences of their children - Chen Fuhui 1986-; Hanna Ragnarsdóttir 1960- (2014)
The aim of this study is to explore what situations immigrant single-parent families face in Iceland, their process of integration into Icelandic society and the educational experiences of their children. This is a qualitative interview study where 11 participants were recruited through a purposive sampling strategy. Data was collected in 2012 through semi-structured in-depth interviews. The main significance of the study is to give a minority group a voice while also providing important information for Icelandic society and educational system. Findings of the study indicate that the families and their children initially experienced difficulties in society and schools, partly related to marginalization and discrimination. However, social support systems, such as support from social networks and financial support from the state, and school support systems, such as special school support, do have positive effects on the lives of these families. According to the findings of this study, it is clear that the work-family conflict is alleviated by the financial and social support system. All the parents interviewed in this study are concerned about preserving their children’s mother tongue, but all of them put their first consideration on their children’s Icelandic language learning. Discontinuities between home and school are also discovered in this study. Most children in this study experienced marginalization in Icelandic schools, particularly in the first few months of attending the schools, when they were rejected by groups of Icelandic children. Markmið rannsóknarinnar er að kanna aðstæður einstæðra foreldra í hópi innflytjenda á Íslandi, ferli aðlögunar þeirra að íslensku samfélagi og reynslu barna þeirra af menntun. Rannsóknin er eigindleg og gagnasöfnun fór fram með viðtölum. Ellefu þátttakendur voru valdir með markmiðsúrtaki. Gagna var aflað árið 2012 í hálfskipulögðum djúpviðtölum. Gildi rannsóknarinnar er fyrst og fremst að ljá minnihlutahópi rödd, en jafnframt að veita íslensku samfélagi og skólakerfi ...